Ecologia de peixes de riachos da bacia do rio Machado, RO: padrões, processos e conservação - Pérez-Mayorga, María Angélica [UNESP] (2015)
In this thesis, the effects of local, landscape and spatial variables on composition, abundance, functional traits and phylogeny of stream ichthyocenoses were analyzed. Based on fish species, environmental and spatial datasets from 52 (2012 samples) and 75 (2011 and 2012 samples) stream reaches located in the Machado River basin, in the state of Rondônia, three chapters were organized. The highlight of the chapter one was the ecological patterns of all species of entire metacommunity and fish assemblages according to their degree of habitat specialization (habitat generalists and habitat specialists). The three cenoses were environmentally structured, suggesting that the niche-based processes explain their structure. In the chapter two, the ecological processes that probably explain the obtained patterns were explored more deeply. Both functional and phylogenetic clustering was confirmed. Environmental variables, such as the proportion of ultisol in the microbasin and of grasses and bared soil in the riparian buffer, structure the assemblages that are associated with degraded streams (DS). On the other hand, the proportion of forest and of oxisoil in the microbasin; coarse litter, shrubs and trees in the stream riparian buffer, structure the assemblages that are associated with the preserved streams (PS). The environment also influences through environmental filter mechanisms, the consumption of algae and the nektonic position in the water column in DS, whereas influences the consumption of invertebrates debris and the nektobenthic position in the water column in PS. The DS and PS position is coincident with the different land uses. DS are concentrated in the central portion of the basin, where the soil is covered by pastures, and PS are in the extremes of the basin, where there are greater proportions of forests. Most species of Siluriformes and of Characidae are associated with DS, on the other hand, Gymnotiformes, some species of ...